PERANCANGAN Application Design and Development Futsal Stadiums in Samarinda 2020 (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The background of this research is its development in the increasingly diverse world of technology and requires field rental service providers to be able to adapt to the competition that is being lived. How service providers are required to provide easy and fast service. This is important because at this time covid-19 is a barrier for someone to warm up the futsal field. The purpose of this study is to develop and analyze: 1. Build a futsal stadium application product for ordering fields using android, 2. The effectiveness of the futsal stadium application in placing orders for service providers. The validation results obtained from material experts i and material experts ii were obtained from the material and content aspects with the percentage from stage i material i giving 73% and material experts ii getting 75%, after revising material i experts giving 90%, and material experts ii gives 91%. In a small-scale trial, the value obtained from service providers is in the very good category with a percentage of 82%. The results of large-scale trials get a very good category with a percentage of 85%. For testing the futsal stadium application product, the average percentage of 90% is included in the very good category. The conclusion in this research is the creation of an android-based futsal field booking application called futsal stadium, and can be downloaded on a smartphone via google drive. The futsal stadium application product can be used to place field orders, as a marketing tool, and speed up transaction times.